The Central Role of Extracellular Vesicles in the Mechanisms of Thrombosis in COVID-19 Patients With Cancer and Therapeutic Strategies - Jing, Haijiao; Zuo, Nan; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Cell and Developmental Biology, 2022)
Cancer patients have increased SARS-CoV-2 susceptibility and are prone to developing severe COVID-19 infections. The incidence of venous thrombosis is approximately 20% in COVID-19 patients with cancer. It has been suggested that thrombus formation has been suggested to correlate with severe clinical manifestations, mortality, and sequelae. In this review, we primarily elaborate on the pathophysiological mechanisms of thrombosis in COVID-19 patients with cancer, emphasize the role of microparticles (MPs) and phosphatidylserine (PS) in coagulation, and propose an antithrombotic strategy. The coagulation mechanisms of COVID-19 and cancer synergistically amplify the coagulation cascade, and collectively promotes pulmonary microvascular occlusion. During systemic coagulation, the virus activates immune cells to release abundant proinflammatory cytokines, referred to as cytokine storm, resulting in the apoptosis of tumor and blood cells and subsequent MPs release. Additionally, we highlight that tumor cells contribute to MPs and coagulation by apoptosis owing to insufficient blood supply. A positive feedback loop of cytokines storm and MPs storm promotes microvascular coagulation storm, leading to microthrombi formation and inadequate blood perfusion. Microthrombi-damaged endothelial cells (ECs), tumor, and blood cells further aggravate the apoptosis of the cells and facilitate MPs storm. PS, especially on MPs, plays a pivotal role in the blood coagulation process, contributing to clot initiation, amplification, and propagation. Since coagulation is a common pathway of COVID-19 and cancer, and associated with mortality, patients would benefit from antithrombotic therapy. The above results lead us to assert that early stage antithrombotic therapy is optimal. This strategy is likely to maintain blood flow patency contributing to viral clearance, attenuating the formation of cytokines and MPs storm, maintaining oxygen saturation, and avoiding the progress of the disease.